Correlação entre as avaliações radiológicas, clínicas e funcionais das alterações pulmonares em crianças e adolescentes com fibrose cística - Flavia Fajardo Linhares Pereira (2011)
Objective: To review the literature, verifying the role of high resolution computed tomography of the chest in the monitoring of children and adolescents with cystic fibrosis. Method: The bibliographic survey was based on information released by the Medline, MD Consult, Highwire, Medscape, LILACS, and direct search of the past 10 years, using the terms cystic fibrosis, tomography, spirometry and children. Results: We have selected 21 original articles on nonsystematic review. The High Resolution Computed Tomography (HRCT) is a good method, since it is recommended to evaluate the lung parenchyma, due to the characteristics of lung impairment in cystic fibrosis. Allows identification of the main changes related to cystic fibrosis bronchiectasis, peribronchial thickening, mucus plugging and hyperinflation / emphysema, as well as consolidation, atelectasis, and bullae. Performed routinely to determine the structural abnormalities, HRCT is also indicated in cases of clinically significant worsening of the patient regardless of age. The question about the best time to perform it also lacks clinical studies and is usually based on service protocols. Comparative studies of spirometry and clinical-radiologic Shwachman-Kulczycki show that a strong positive correlation between this and FEV1 (r=0.75, P<0.001 and r=0.50, P 0.01) but while HRCT showed significant structural changes spirometry showed minimal progression or improvement in the standard. Great attention should be given to the issue of ionizing radiation and the amount of radiation to which the patient is exposed. Conclusion: There is still a role for HRCT in monitoring patients with Cystic Fibrosis. As low-dose techniques are developed one can glimpse the HRCT as an excellent method for evaluation of pulmonary involvement of young pacient under the age of 6 years, and therefore unable to perform pulmonary function tests